Approaches and Informatics Tools to Assist in the Integration of Similar Clinical Research Questionnaires - Brandt, C. A.; Cohen, D. B.; Shifman, M. A.; Miller, P. L.; Nadkarni, P. M.; Frawley, S. J. (Methods of Information in Medicine, 2004)
Objective: The integration of similar clinical research questionnaires is a complex process that can benefit from informatics approaches and tools that provide a systematic structure for performing mapping and integration. This systematic approach is necessary to address complex issues in integration such as data heterogeneity, differing levels of granularity of questions and responses, and other issues involving semantic differences. Informatics tools and approaches have been successfully applied to various standard clinical vocabulary integration processes but not for questionnaire integration or mapping.Methods: A systematic approach to questionnaire integration was developed in the context of a collaboration of researchers using Trial/DB, a database designed to support clinical research. This approach was applied to the integration of questionnaires involving breast cancer risk factors from each of three research sites.Results: From 375 questions on the three original questionnaires, we identified 65 concepts that were measured by two or three of the sites. An algorithm was developed and used to formalize the process of mapping questions and answers across the questionnaires. The approach was applied to previously collected data and prospective data in disparate database systems to import and merge the data from these three sites into Trial/DB.Conclusion: Informatics tools that support a systematic approach to mapping questionnaires can be used throughout the research process from questionnaire integration and creation, legacy data integration to data library maintenance and curation.
Keywords: Vocabulary mapping; data integration; pooled analysis; surveys; questionnaires